PENINGKATAN HASIL BELAJAR OPERASI HITUNG CAMPURAN DENGAN MODEL KOOPERATIF TIPE NHT - Sari, Sistri Wanola; Ahmad, Syafri; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
ABSTRACT The purpose of this research is to describe the improvement of operational learning result with NHT type cooperative model in elementary school. The type of this research is Classroom Action Research (PTK) using qualitative and quantitative approach which includes planning, implementation, observation and reflection. The subjects of this study were teachers and students of class IV with a total of 19 students. The result of RPP Cycle I was 82,70%, cycle II to 92,31%, teacher cycle 70,32%, cycle II to 90,63%, student cycle I 68,75%, cycle II to 87, 51%. Student learning outcomes cycle I average 67,72, cycle II to 82,59. Thus, it is concluded that the jigsaw type cooperative model can improve the learning outcomes of waking properties. Keywords: Learning result of mixed count operation, cooperative model of NHT type